Have the government measures been enough to restore stakeholder confidence in the banking system? An Analysis of the 2007 Financial Crisis - Aggarwal, Vikas (2009)
“In good times, people trust. They make decisions spontaneously. They know instinctively that they will be successful. They suspend their suspicions. Asset prices will be high and perhaps also increasing. As long as people remain trusting, their impulsiveness will not be evident. But then, when the confidence disappears, the tide goes out. The nakedness of their decisions stands revealed” (Akerlof and Shiller, 2009:13)